Developing Gastronomic Tourist Loyalty through Local Food Authentication, Destination Image and Travel Experiences - Thayarnsin, Sarinya La-ong-in (Journal of Social Sciences and Humanities Research in Asia, 2023)
The tourism industry acknowledges gastronomic tourism as one of its most crucial topics; however, research on the loyalty of gastronomic tourism destinations is scarce. Therefore, this study aims to propose and verify a conceptual model of tourist destination loyalty in the gastronomy industry, considering the concept of local food authentication, tourist experience, and destination image as gastronomy tourism from the perspectives of Thai or domestic tourists. The constructs’ factorial validity, the proposed model’s goodness of fit, and the hypotheses are assessed using the statistical software for Social Sciences. The model provides an acceptable fit to the data ((X2=1041.399, df=369, GFI=.984, NFI=.954, CFI=.948, AGFI=.968, RMSEA=.073), The research results demonstrate a considerable impact of local food authentication on the tourist experience and the image as a gastronomy tourism destination, which in turn influences destination loyalty. While local food authentication statistically affects destination loyalty, the tourist experience directly affects the destination’s image. Consequently, the most significant contribution of this research is that stakeholders have a better understanding of the critical factors associated with applying for gastronomy tourism; thus, strategies and the concept of creativity can be proposed to improve local food authenticity as well as a tourist experience, thereby enhancing destination image and loyalty in the context of gastronomy tourism.